Engagement e interacción de Disney+ Latam con sus usuarios digitales - Gamarra Galindo, Sandra Patricia (2023)
Internet and the consumption of audiovisual content are two inseparable terms. The emergence of new technologies has changed how global audiovisual content is consumed. Citizens watch online content more frequently, which favours the emergence of new commercial models that satisfy these needs. In this convergence model, DisneyPlus Latam plays an essential role as a platform. The company entered the video streaming business to carve out a space in the television and film industries. It went from being a reasonably successful animation studio to a complete entertainment experience, which includes theme parks, merchandise, cruises, and more. The purpose of this research is to analyze the social media management of DisneyPlus Latam during February 11th and March 11th, 2022, how it manages its communication on social networks, how the public receives it, and to determine the level of response and interaction behind it. The method used is mixed; content analysis and impact according to social media content were conducted qualitatively, while the reactions of followers, number of posts, likes, shares, followers, and times shared were measured quantitatively. The research shows that DisneyPlus Latam has not only completely changed the way to access audiovisual content but has also innovated how to share content through social networks to position its products among subscribers.